2016
DOI: 10.1177/1054773815618607
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of Stress of Conscience, Perceptions of Conscience, Burnout, and Social Support Before and After Implementation of a Participatory Action-Research-Based Intervention

Abstract: Interventions aiming to constructively address stress of conscience are rare. The aim of the study was to compare assessments of stress of conscience, perceptions of conscience, burnout, and social support among health care personnel (HCP) working in municipal residential care of older adults, before and after participation in a participatory action research (PAR) intervention aiming to learn to constructively deal with troubled conscience. Questionnaire data were collected at baseline and at follow-up (1-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…Stress of conscience and ethical dilemmas are a topical issue in healthcare 6,[45][46][47] and need to be examined from different angles, for example, the exact mechanisms and process involved to work intensification that may increase stress of conscience. Follow-up research should therefore utilize a longitudinal mediator setting to establish whether the reasons leading to increasing stress of conscience, for example, are increasing pace of work and workload that impair adequate care or something else.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Stress of conscience and ethical dilemmas are a topical issue in healthcare 6,[45][46][47] and need to be examined from different angles, for example, the exact mechanisms and process involved to work intensification that may increase stress of conscience. Follow-up research should therefore utilize a longitudinal mediator setting to establish whether the reasons leading to increasing stress of conscience, for example, are increasing pace of work and workload that impair adequate care or something else.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…They found that the non-parametric test (Kruskal-Wallis) showed a significant reduction in burnout score post-intervention, however conducting a parametric test ANOVA did not find a statistical significance in burnout scores in the same study. No statistically significant reduction score post-intervention was found by two other intervention studies (Fukuda et al (2018), Ericson-Lidman & Ahlin (2017).…”
Section: Resultsmentioning
confidence: 75%
“…Health care professionals cannot tolerate extreme busyness over time without compromising either the quality of the care they provide or their own health (Ericson‐Lidman & Åhlin, 2017). For many nurses, maladministration of relational tasks and concrete and visible negligence, such as failing to provide for the fluid and nutritional needs of patients, are perceived as a confession of failure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is possible to learn solutions. Reflection allows one to review knowledge about the actors' own situations and to develop a knowledge base through which nurses can decide on meaningful and feasible actions to be undertaken (Ericson‐Lidman & Åhlin, 2017). Reflection may be a way to address busyness constructively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation